Frederick Douglass : America's prophet - Dilbeck, D. H. (The University of North Carolina Press, 2018)
"Frederick Douglass was born into slavery on Maryland's Eastern Shore and became an extraordinary champion of liberty and equality. Throughout his long life, Douglass was also a man of profound religious conviction. ... With an eye toward explaining how Douglass's religious beliefs shaped his influential public career, Dilbeck retells the story of Douglass's life"--